Impacts of turmeric and its principal bioactive curcumin on human health: Pharmaceutical, medicinal, and food applications: A comprehensive review - El-Saadony, Mohamed T.; Yang, Tao; Korma, Sameh A.; Sitohy, Mahmoud; Abd El-Mageed, Taia A.; Selim, Samy; Al Jaouni, Soad K.; Salem, Heba M.; Mahmmod, Yasser; Soliman, Soliman M.; Mo’men, Shaimaa A. A.; Mosa, Walid F. A.; et al. (Frontiers in Nutrition, 2023)
The yellow polyphenolic pigment known as curcumin, originating from the rhizome of the turmeric plant Curcuma longa L., has been utilized for ages in ancient medicine, as well as in cooking and food coloring. The biological activities of turmeric and curcumin have been thoroughly investigated recently. The studies mainly focused on their antioxidant, antitumor, anti-inflammatory, neuroprotective, hepatoprotective, and cardioprotective impacts. This review seeks to provide an in-depth, detailed discussion of curcumin usage within the food processing industries and its influence on health support and disease prevention. Curcumin's bioavailability, bio-efficacy, and bio-safety characteristics, as well as its side effects and quality standards, are also discussed. Finally, curcumin's multifaceted uses, food appeal enhancement, agro-industrial techniques counteracting its instability and low bioavailability, nanotechnology and focused drug delivery systems increasing its bioavailability, and prospective clinical use tactics are all discussed.